Characterization and evaluation of bilayer coating for enhanced localization and sustained drug delivery for fibrosis-induced ureteral stricture - Chin, Jia Wen (2016)
Ureteral stricture is the second most prevalent urologic condition. In particular, fibrosis-induced ureteral strictures are the excessive deposition of collagen due to scarring. Fibroblast proliferation can be managed with Mitomycin C (MMC) drug that has been widely documented in cancer treatments. However, an issue associated with drug release in the ureter is the low drug permeability of transitional membrane of ureter tissues. The drug permeability barrier can be overcome by direct contact of the drug and urothelium. The usage of a bilayer coating, consisting of a hydrogel layer and a drug-loaded polymer layer, allows for direct contact with the ureter walls upon swelling and drug delivery through the urothelium. This will enhance the local delivery of drugs and sustain drug delivery to treat chronic conditions. This project aims to synthesize a bilayer coating for enhanced localization and drug release over four weeks. PEGDA hydrogels of different concentration (5.0%, 7.5%, 10.0%) fabricated with 0.1% Irgacure 2959 were used for characterization through mass measurement and degradation studies. Ureteral stents of various thickness (20um, 50um, 100um) coating and drug concentrations (2.5%, 5.0%, 7.5%) were fabricated using spraycoating, and in vitro drug release studies were analysed using high-performance liquid chromatography. Mass and degradation studies of varied hydrogel concentration demonstrated that hydrogels of 7.5% and 10.0% concentration showed no leaching of by-products through a four-week period and are stable for usage through a four-week period, which is the therapeutic time window. The in vitro release studies highlighted that an increase in polymer coating thickness decreased the rate of drug released resulting from increased diffusion path length. Drug release rates also demonstrated a decrease with time due to an increase in diffusion path length. In addition, an increase in initial drug concentration decreased the drug released from PLC polymer matrix. However, drug concentration at 2.5% showed a discrepancy from predicted results. This discrepancy could be due to the lack of uniform drug dispersion and fabrication methods. Drug release rates of polymer layer exposed to surface modifications of ii UV radiation, plasma treatment and hydrogel layer did not show any significant difference when compared to stents coated with only the drug-loaded polymer coating. Hence, the hydrogel layer did not retard the diffusion of drug molecules to the surrounding aqueous medium. Exposure to UV radiation and plasma treatment likewise did not degrade polymer and drug on the coating surface. However, this study was not conducted through a four-week period as hydrogel layer had delaminated by the third week. Future work would be done to improve the adhesion of hydrogel and polymer layer. Furthermore, cell assays would be conducted to determine the therapeutic window of MMC drug.